The cardiorenal syndrome - Klug, Eric (SA Heart Journal, 2017)
The progress made in the medical and device therapy of chronic heart failure (CHF) due to left ventricular systolic dysfunction has heralded new problems. Patients present having survived longer with CHF, but with minimal exercise reserve and renal dysfunction with or without systemic congestion. We now recognise this clinical presentation as the cardiorenal syndrome. The classic hemodynamic/neurohormonal understanding of the syndrome explains only partly the pathophysiology, and it is now recognised that the kidney early on in a heart failure patient shows abnormal handling of a sodium load and changes in renal blood flow. Renal dysfunction is commonly seen in patients with CHF and the higher the level of the admission serum creatinine as well as an increase in serum creatinine during hospitalisation portends a graver prognosis. Chronic kidney disease itself is associated with a greater incidence of heart failure, but unravelling the pathophysiological mechanisms involved in this reciprocal relationship between the heart and the kidneys remains elusive. Essentially the problem remains in trying to maintain optimal fluid balance while preserving renal function.